(untitled) (Revista Brasileira de Contabilidade e Gestão, 2022)
Objective: This article aims to describe the people management processes used by the Cresol Credit Union in a branch of the Alto Uruguay Region, in Brazil. (ii) Method: The methodology used has consisted of a qualitative approach of exploratory-descriptive nature, and the technical procedure used has been the case study. For data collection, interviews, document analysis, and participant observation have been carried out. (iii) Results: The results of this study have shown that the union develops actions in the area of people management according to the processes established by Chiavenato (2014). In this sense, the Cresol branch has practices in recruitment and selection of employees, work orientation, and training and advising of staff, in addition to providing benefits associated with compensation and the maintenance of staff. (iv) Contributions: Finally, the study considers that the union, by implementing actions in the area of people management, is investing in the human capital of the institution in order to offer the best service to its partners and for the maintenance and acquisition of new members to the staff.